The effect of questioning gender stereotype threat on girl’s standing long jump performance - Elahe Naderi Dehkordi; Ebrahim Moteshareie; Behrooz Abdoli; Esmaeel Saemi; Maxime Deshayes (BMC Psychology)
Abstract Background Over the past few years, the sport psychology literature has established that gender stereotype threat (ST) is one of the factors that can impair girls’ performance. However, few studies have attempted to annihilate these negative effects. The purpose of the current study was to investigate whether questioning gender ST can mitigate the classical decline in girls’ standing long jump (SLJ) performance. Methods The participants were 120 girls (Mage = 10.74 ± 0.85 years), selected through convenience sampling and randomly assigned to three groups: the gender ST group (n = 40), the questioning group (n = 40), and the control group (n = 40). For all groups, baseline performance (i.e., SLJ) was measured by a female researcher following a warm-up period. In the experimental phase, the control group repeated the baseline conditions; the gender ST group completed the same test but was evaluated by a male examiner (i.e., implicit stereotype induction), while participants in the questioning group were assessed after receiving questioning statements while performing the task in front of a male examiner. Results The results of the present study showed that the induction of a gender ST leads to a decrease in SLJ in girls. Additionally, if these inducing conditions of gender ST are accompanied by a questioning condition, the negative effects of gender ST can be reduced, and SLJ in girls does not decline. Conclusion Based on our findings, this intervention is recommended as a simple, inexpensive, and quick solution for mitigating the negative effects of gender ST on girl’s motor performance.